Into the Grey Zone: A Neuroscientist Explores the Border Between Life and Death by Adrian Owen - Kelly, Edward F. (Journal of Scientific Exploration, 2018)
Dramatic modern advances in emergency and resuscitation medicine, starting perhaps with the development of effective mechanical ventilators in the mid-20th century, have created a large class of persons who in earlier times would almost certainly have died, but who can now go on existing, suspended at least temporarily in a state somewhere between death and the conscious life they formerly pursued. A very wide range of brain injuries lead first to coma, in which the patient shows no sign of conscious awareness, or even of wakefulness, in which eye openings and closings indicate the presence of a sleep/wake cycle unconsciously mediated by structures in the brain stem. Following emergence from coma, which may take days to months or more if it happens at all, patients typically show signs of wakefulness without conscious awareness – they are then in a so-called vegetative state (VS). For many this state becomes permanent, but some go on to a more recently described condition called the minimally conscious state (MCS), in which signs of conscious awareness can be detected by careful neurological examination (see Laureys & Tononi, 2009, chapter 14). A very few such persons ultimately progress to more or less full recovery, but another and particularly horrifying possible outcome is the “locked-in” state, in which a patient is fully conscious but has extremely little or no capacity for voluntary motor action. A famous modern example is that of Jean-Dominique Bauby, author of The Diving Bell and the Butterfly, who suffered a stroke to his upper brainstem and awakened 20 days later to find himself fully conscious but capable only of blinking his left eye. A tiny fraction of surgical patients find themselves in similarly terrifying conditions caused by the combination of muscle relaxants with insufficient levels of anesthetic agents (Kelly et al., 2007, p. 387 n. 18).